2023
DOI: 10.3390/pr11030825
|View full text |Cite
|
Sign up to set email alerts
|

Study on Verification Approach and Multicontact Points Issue When Modeling Cyperus esculentus Seeds Based on DEM

Abstract: In this paper, the Multisphere (MS) models of three varieties of Cyperus esculentus seeds are modeled based on DEM. In addition, for comparison, other particle models based on automatic filing in EDEM software are also introduced. Then, the direct shear test, piling test, bulk density test, and rotating hub test are used to verify the feasibility of particle models of Cyperus esculentus seeds that we proposed. By comparing the simulated results and experimental results, combined with the CPU computation time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
0
0
Order By: Relevance
“…In order to avoid the issue of multiple contact points, the HMNS model was adopted to establish a model of ellipsoidal seed particles. The result supported the recent study in Xu's finding, which reported that, with an increasing number of contact points, the rebound height decreased when creating the particle model based on the MS method [34]. It is important to note that the assumption of ellipsoidal seeds as dry particles was not entirely accurate, particularly in the case of a single seed in the calibration test (a freefall experiment).…”
Section: Contact Model Selectionsupporting
confidence: 88%
“…In order to avoid the issue of multiple contact points, the HMNS model was adopted to establish a model of ellipsoidal seed particles. The result supported the recent study in Xu's finding, which reported that, with an increasing number of contact points, the rebound height decreased when creating the particle model based on the MS method [34]. It is important to note that the assumption of ellipsoidal seeds as dry particles was not entirely accurate, particularly in the case of a single seed in the calibration test (a freefall experiment).…”
Section: Contact Model Selectionsupporting
confidence: 88%
“…Table 1 shows the high (+1) and low (−1) levels of parameters A~I in the PB test. Based on EDEM software (EDEM version: EDEM 2018, DEM Solutions, Edinburgh, UK, 2002), a soil particle model was established using a multisphere combination method for simulation experiments [32][33][34], which cannot reflect the magnitude of the soil water content. The bonding between particles needed to be characterized by the JKR surface energy, which was subsequently calibrated by the simulation test in this paper, and the Rayleigh time step of the simulation test was 1.5 × 10 −4 s. The simulation screenshot of the soil AoR test is shown in Figure 6…”
Section: Calibration Of the Dem Parameters Of The Soda Saline-alkali ...mentioning
confidence: 99%